2006
DOI: 10.1016/j.jacc.2006.07.048
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Strain and Torsion Quantified by Cardiovascular Magnetic Resonance Tissue Tagging

Abstract: Accurate quantification and timing of regional myocardial function allows early identification of dysfunction, and therefore becomes increasingly important for clinical risk assessment, patient management, and evaluation of therapeutic efficacy. For this purpose, the application of tissue Doppler echocardiography has rapidly increased. However, echocardiography has some major inherent limitations. Cardiovascular magnetic resonance imaging with tissue tagging provides highly reproducible data on myocardial func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
145
1
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 195 publications
(155 citation statements)
references
References 75 publications
(69 reference statements)
7
145
1
2
Order By: Relevance
“…There have been some studies demonstrating the paradoxically increased LV torsion with normal EF in patients with diabetes, aortic stenosis, and hypertrophic cardiomyopathy. [22][23][24][25][26] Because the changes in torsion occur far before irreversible tissue damage, this may be considered as an early indicator of systolic dysfunction. We found that the increase in basal-to-apical torsion was mainly derived from the increase in basal rotation.…”
Section: Discussionmentioning
confidence: 99%
“…There have been some studies demonstrating the paradoxically increased LV torsion with normal EF in patients with diabetes, aortic stenosis, and hypertrophic cardiomyopathy. [22][23][24][25][26] Because the changes in torsion occur far before irreversible tissue damage, this may be considered as an early indicator of systolic dysfunction. We found that the increase in basal-to-apical torsion was mainly derived from the increase in basal rotation.…”
Section: Discussionmentioning
confidence: 99%
“…Cine imaging with myocardial tagging was applied to create non-invasive markers (tags) within the myocardium for calculation of strain [11]. Three short-axis tagged images with complementary spatial modulation of magnetization tagging for improved strain calculations were acquired as previously described [17].…”
Section: Cmrmentioning
confidence: 99%
“…Insights into the mechanism and causative factors of altered energy metabolism could therefore be of clinical importance in risk stratification and the development and application of (new) therapeutic approaches. Recent advances in imaging techniques offer the possibility to accurately assess myocardial oxygen consumption (MVO 2 ), regional mechanical work and tissue characteristics non-invasively using dynamic positron emission tomography (PET) [9,10] and cardiac magnetic resonance imaging (CMR) [11][12][13], respectively. The present study was conducted to identify the determinants of impaired myocardial energetics and efficiency in patients with symptomatic HCM with the use of these currently available advanced imaging techniques.…”
Section: Introductionmentioning
confidence: 99%
“…In the 1990s, studies performed by a different type of magnetic resonance imaging (MRI), tagged MRI, [14][15][16] allowed for visualization of the movements of the heart on different axes by non-invasive methods [14,[17][18][19][20][21][22]. Although the temporal resolution of MRI is low, it was used in pilot studies to describe the rotation mechanics and has an important place in the validation of tissue Doppler-based (23,24) or speckle tracking-based echocardiography studies [20][21][22]25] bCurrently, tagged MRI is generally used for research purposes, and in particular, speckle tracking-based echocardiography techniques make it possible to perform practical and reproducible measurements for current research in a cost effective manner [26,27].…”
Section: Deformation Imagingmentioning
confidence: 99%